The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/jso.23223
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of rectal gastrointestinal stromal tumors

Abstract: Preoperative imatinib leads to downsizing of the tumors in Group 1. However, it has not led to less extensive surgery. The DFS is longer in patients treated with pre- and post-operative imatinib, without an effect on OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 13 publications
5
54
2
3
Order By: Relevance
“…Our cohort of patients was predominantly male (73.3%), which is similar to data in other studies [9,10]. The tumor size of rectal GISTs patients was small with a median size of 5 cm, which was in agreement with the data obtained by Jakob et al [15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our cohort of patients was predominantly male (73.3%), which is similar to data in other studies [9,10]. The tumor size of rectal GISTs patients was small with a median size of 5 cm, which was in agreement with the data obtained by Jakob et al [15].…”
Section: Discussionsupporting
confidence: 92%
“…This marker is expressed in more than 90% of stromal tumors. Tielen et al [10] reported that 32 patients with rectal GISTs had 88% CD117-positive expression rate. Furthermore, high positive expression of CD117 (93%) for this type of lesion was reported [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, those GISTs arising in anatomically compromised locations would be a preferred target population, and particularly rectal GISTs, that usually have responsive KIT exon 11 mutations and involve challenging surgeries [Jakob et al 2013;Tielen et al 2013].…”
Section: Neoadjuvant Imatinib In Gistsmentioning
confidence: 99%
“…In selected cases preoperative imatinib treatment may reduce tumour size and facilitate surgery, especially when GIST is located in the rectum [2,3] or when gastric GIST is large in size [4]. Preoperative imatinib may allow organ sparing and preserve the gastrointestinal tract function and continuity.…”
Section: Introductionmentioning
confidence: 99%